Service management theory and practice - Bryson, John R.; Sundbo, Jon; Fuglsang, Lars; Daniels, Peter (Palgrave Macmillan, 2020)
"This textbook offers a fully integrated approach to the theory and practice of service management, exploring the operational dynamics, management issues and business models deployed by service firms. It builds on recent developments in service science as an interdisciplinary research area with emphasis on integration, adaptability, optimization, sustainability and rapid technological adoption. The book explores seven fundamental processes that are key to successfully managing service businesses, helping students gain insights into: - how to manage service businesses, with coverage of both small firms and large transnationals - service business models, operations and productivity - managing service employees - how service firms engage in product and process innovation - marketing, customers and service experiences - internationalization of service businesses - the ongoing servitization of manufacturing This unique textbook is an ideal resource for upper undergraduate and postgraduate students studying service businesses and practitioners."--Back cover.